Hubungan Body Image dan Perilaku Makan dengan Status Gizi pada Remaja SMA di Kecamatan Banjarsari Surakarta - Niza, Tri Fajra; Puspita Sari, Dyah Intan; Firmansyah, Firmansyah (Ranah Research : Journal of Multidisciplinary Research and Development, 2025)
Adolescence is a transitional period from childhood to adulthood, during which rapid physical, mental, and emotional changes occur. During this period, adolescents begin to form their identity and search for identity. One of the things that develops is awareness of physical appearance, called body image. Body image shows how a person views body shape, body size, and overall appearance, both from the assessment of themselves and others. Perception of body image can affect eating behavior. Adolescence who have a negative body image may go on strict diets or eat emotionally without control. Both of these behaviors can lead to an unbalanced nutrient intake. This study aims to analyze the relationship between body image, eating behavior, and nutritional status of high school adolescents in Banjarsari District, Surakarta. The method used was a cross-sectional study with 154 respondents selected randomly proportionally. The tool used was the body image questionnaire (BSQ-34) containing 34 questions covering 4 aspects: perception of body shape, comparison with others, excessive focus on the body, and changes in body perception. The eating behavior questionnaire (DEBQ-28) contains 28 questions covering 3 aspects of eating behavior: emotional eating, eating due to external influences, and controlling appetite. Nutritional status was measured using anthropometric methods, including body weight and height, which were then analyzed using the Body Mass Index for Age (BMI/A). Data were analyzed using the Spearman Rank test to see the relationship between body image, eating behavior, and nutritional status. The results showed that 84.4% of adolescents in Banjarsari District had a positive body image. Adolescents tended to engage in external eating behaviors, with the highest average score of 26.84. The majority of adolescents had normal nutritional status (64.3%). The study found a relationship between body image (p < 0.001), external eating behavior (p = 0.027), and restrained eating behavior (p = 0.000) with nutritional status. However, there was no relationship between emotional eating behavior (p = 0.830) and nutritional status among adolescents in Banjarsari District.